Silver Mirror Reaction with Polystyrene Nanoparticles Template - Jun Yin, Fu; Hong Zhang, Li; Zhao, Hong; Zhao, Gui; You Xu, Xing (Asian Journal of Chemistry, 2013)
Two-dimensional silver nanocavity array was fabricated by templating of the periodically assembled polystyrene nanoparticles via silver mirror reaction. We reveal the mechanism of silver growth in the space among the polystyrene nanoparticle. Polystyrene is made of emulsifier-free emulsion polymerization. The silver grow does not depend on specific position on the polystyrene nanoparticle surface, as homogeneous distribution of the Ag core, relying on active surface on Ag core and the left channels, silver grow from silver nanoparticls to two-dimensional silver nanocavity array.